DIRECTIONS OF EXPANSION FISCAL SPACE IN TERMS OF FINANCIAL INSTABILITY - Diana Osetska (Izdevnieciba "Baltija Publishing", 2016)
The paper identifies substantial reasons, the principles, conditions and institutional mechanisms for expanding fiscal space as a reflection of the objective need for development and modernization of the financial system of Ukraine in the European integration. The basic directions of expanding fiscal space in the context of revenues based on innovations in tax legislation. By applying institutional approach, theoretical principles and practical recommendations to improve the sustainability of public finances in the process of expanding the fiscal space are grounded. The research outlines the political and institutional changes that can help expand the fiscal space, particularly as a result of administrative reform with the reduction of wasteful expenditure, tax reform, which has a stimulating effect, fiscal reform, which introduces new fiscal "rules". Attention is paid to the formation of fiscal space in Ukraine to macroeconomic stabilization and economic reform for economic growth. It is proved that due to the expansion of fiscal space in national economies new approaches to unification of formal and informal regulatory rules should be implemented both in scientific and in economic aspects.